MODELIZACIÓN DE LA CALIDAD DEL SUELO ASOCIADA A PLAGUICIDAS COMO UNA MODIFICACIÓN DEL MÉTODO DEL INSTITUTO BATELLE – COLOMBUS - Agustín Leiva Pérez; Joffre Andrade Candell; Sonia Elisa Peñafiel Acosta; Carmen del Rocío Zavala Navarrete; Eduardo Antonio Muñoz Jácome (European Scientific Journal, ESJ, 2015)
The study dealed on the design and the application of a mathematical model for the determination of the soil quality, associated to pesticides of more common use. The pattern consisted on an extensive modification of the Index of Water Quality developed by Institute Batelle Colombus, USA, to be applied to the soil (Index of Soil Quality Associated to Pesticides, ISQAP), in relation with pesticides. A wide group of values of concentrations of these compounds was used and, once proven the adjustment of the pattern to the same ones, it was proceeded to apply it using concentrations obtained data for agricultural soils of the Caluma low part, Bolivar county, Ecuador. The results demonstrated an Index average value of 42%, indicative of an Environmental Quality Level around 0.61; this is, "bad"; being recommended the amplification of the study to other areas of the studied microcuenca, as well as to others in those that is suspected of an indiscriminate pesticides employment, as well as the socialization of this work among the territory farmers population, propitiating their motivation in the good use of these compounds.